Elevated amputation rates in COVID‐19 survivors: Insights from a large‐scale Japanese cohort study - Daisuke Miyamori; Shuhei Yoshida; Masanori Ito (Journal of Diabetes Investigation)
ABSTRACT Objective COVID‐19 has been linked to increased vascular complications, but its long‐term impact on amputation rates is unclear. This study evaluated amputation risk post‐COVID‐19 using a nationwide insurance claims database in Japan. Methods We conducted a retrospective cohort study using data from the National Database of Health Insurance Claims and Specific Health Checkups of Japan. COVID‐19 cases were identified via insurance payment waivers, and amputations were defined by procedure codes. Propensity score matching created balanced cohorts of COVID‐19 exposed and unexposed individuals. Matched cohorts were compared for amputation incidence, calculating incidence rate ratios (IRRs), and differences (IRDs). Sensitivity analyses examined outcomes at different time points, and subgroup analyses stratified results by key characteristics. Results This study included 3,098,948 matched pairs. Over a median follow‐up of 7 months, 286 amputations occurred in the COVID‐19 group vs 123 in controls (IRR 2.33, 95% CI 1.88–2.90; IRD 5.57 per 1,000,000 person‐months, 95% CI 4.22–6.92). The elevated risk persisted beyond 2 years post infection (IRR 2.03, 95% CI 1.31–3.20). Subgroup analyses showed higher risks in individuals with higher comorbidity burden (Charlson Comorbidity Index [CCI] ≥2; IRR 2.45 95% CI 1.92, 2.79) vs lower comorbidity burden (CCI 0–1; IRR 0.71 95%CI 0.29, 1.71) with significant interaction (P = 0.04). Conclusions Amputation rates increased among COVID‐19 survivors, persisting for over 2 years post infection. The interaction between COVID‐19 and comorbidity burden highlights the need for vigilant long‐term monitoring and management of vascular complications in COVID‐19 survivors, particularly those with multiple comorbidities.